Traditional Uses, Phytochemical Constituents and Pharmacological Properties of Averrhoa carambola L.: A Review - Luan, Fei; Peng, Lixia; Lei, Ziqin; Jia, Xiyu; Zou, Junbo; Yang, Yan; He, Xirui; Zeng, Nan (Frontiers in Pharmacology, 2021)
Averrhoa carambola L. (star fruit), as a cash crop for its edible fruits, is extensively cultivated in southern China, Southeast Asia, India, and northern South America. It has been frequently used for treating the diabetes and diabetic nephropathy, arthralgia, vomiting, lithangiuria, coughing and hangovers, and chronic paroxysmal headache for thousands of years. A. carambola is sweet and juicy taste, and frequently utilized to prepare the fruit salads and fruit platters or as garnish in cocktail drinks and beverages or squeeze in to juice to be served as a functional beverage or produce jellies, ice creams, preserves, sweets and cordial concentrates. Currently, approximately 132 ingredients have been successfully isolated from the various medicinal organs of A. carambola. Among them, flavonoids, benzoquinone, and their glycosides have been considered as the biologically active components are responsible for their multiple pharmacological properties. Different pharmacological studies demonstrate that the crude extracts or individual compound from A. carambola exerts multiple biological activities, such as anti-hyperglycemic, anti-obesity, anti-hyperlipidemic, anti-oxidant, anti-tumor, anti-inflammatory, hepatoprotective, cardioprotective, anti-hypertensive, neuroprotective, and others both in vivo and in vitro. A. carambola is a valuable traditional Chinese medicine source with therapeutic potential on multiple diseases especially diabetes and diabetes-related diseases, and it is very promising to be fully utilized in the development of functional food and pharmaceutical industry. Nevertheless, all reported biological activities were conducted in vivo and in vitro and a gap in research regarding clinical settings still exists. Hence, in-depth research on clinical trials to investigate the pharmacological activity, clinical efficacy and safety of A. carambola are very necessary. It goes without saying that A. carambola appear to have great developing potential in the fields of functional food and modern medicine. The opportunities and challenges co-exist. Therefore, this review provides a comprehensive and systematic overview of current progress concerning the botanical description, ethnomedicinal practices, phytochemical compositions, pharmacological properties, and toxicities reported for A. carambola, which will put forward a valuable reference for further developments and applications of A. carambola in the fields of pharmaceutical industry and functional food.